Organizing citizenship behavior, work, values, job performance and profile of the Philippine army education and training staff: toward achieving military service excellence - TSG BOB G NO (AGS) PA (Parañaque City: Olivarez College, 2020)
In contemporary military organizations, citizenship behavior is important to really make it successful, such that members should engage in helpful behaviors, like being loyal, committed, obedient and compliant to reasonable organizational rules and regulations. Likewise, work-values are inseparable to man which is believed to have big influence in the job performance of the military men. This study was undertaken to find out the significant relationship among organizational citizenship behavior, work values, job performance and the profile of the Philippine Army Education and Training staff toward achieving military service excellence. The data were gathered from 75 Non-Commissioned Officers and 75 Civilian Employees in the Education and Training Management of Philippine Army sampled using purposive quota sampling technique. It probed on Quantitative Descriptive and Evaluative Method using self- made survey questionnaire, casual interview and actual observations as the principal means of gathering the data. Percentage, weighted mean, Independent t-test, and Pearson r correlation coefficient. In line with the foregoing, the study focused on the five (5) organizational citizenship behaviors, namely: (1) altruism, (2) courtesy, (3) civic virtue, (4) sportsmanship, and (5) conscientiousness. The work values which was based from Cervera's Filipino Work Values Scale centered only to the three categories, namely: (1) environmental, (2) familial, and (3) interpersonal, while the job performance was determined through their rating in the individual performance evaluation using the Armed Forces of the Philippines Performance Evaluation Report (AFPPER) from 2018 to 2019. Additionally, the personal profile only included their age, gender, educational attainment, length of service and rank. Results showed no significant difference in the organizational citizenship behavior, work values, and job performance of the two groups of respondents. However, all these variables were significantly interrelated to each other. Hence, the citizenship behaviors and the working relationship of the Philippine Army education and training staff must be strengthened. In order for them to have a happy, successful and fulfilling life, they must act upon their values, both in personal life and at work, more so, in achieving military service excellence.
Master Thesis
Keywords: Organizational citizenship behavior; Work values; Service excellence